Altman Z-Score Model to Analyze Bankruptcy of Islamic Commercial Bank POJK No. 12/POJK.03/2020 - Nur Ellyanawati Esty Rahayu; Usmansyah Usmansyah (LAA MAISYIR: Jurnal Ekonomi Islam, 2021)
This study aims to analyze the financial performance of Islamic Banks BOOK 1 with the existence of Financial Fervices Authority (OJK) Regulation No. 12/POJK.03/2020 concerning Commercial Bank Consolidation which stipulates a bank's core capital of at least IDR 3 trillion in 2022. This study employed the Z-Score data analysis method to predict bankruptcy by taking samples of PT Bank Syariah Bukopin, PT Bank Victoria Syariah, and PT Bank Aladin Syariah Tbk. The results of the Z-Score calculation are used to improve financial performance in order to attract investors and determine a strategy for increasing core capital to comply with the POJK provisions on commercial bank consolidation. Banks can determine the strategy that the author recommends to comply with the POJK provisions, including: 1) Merger, consolidation, or integration 2) Bank takeover 3) Increase in minimum core capital through the issuance of new shares (right issue) for banks that have been listed on the Indonesia Stock Exchange, additional core capital from the parent bank, or exploration of new investors both from within the country and abroad.